IKLIM ORGANISASI DI BALAI BESAR PENJAMINAN MUTU PENDIDIKAN PROVINSI SUMATERA BARAT - ayu henirwan, mutya; Achyar, Novriyanti; Syahril; Setiawati, Merika (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research is motivated by the importance of organizational climate in creating a conducive work environment and supporting the effective implementation of employee duties. A good organizational climate plays a role in improving work coordination, employee motivation, the quality of the work environment, and communication, thus optimally achieving organizational goals. However, the conditions of work coordination, employee motivation, the work environment, and communication require continuous attention to ensure the creation of an organizational climate that supports organizational effectiveness. Therefore, this study aims to describe the organizational climate at the Center for Education Quality Assurance in West Sumatra Province based on indicators of work coordination, employee motivation, the work environment, and communication. This research used a quantitative approach with descriptive methods. The study population consisted of 120 employees, with a sample of 97 employees determined using proportional random sampling. Data were collected using a Likert-scale questionnaire that met validity and reliability requirements. Data were then analyzed using descriptive statistics by calculating the average value (mean). The results indicate that the organizational climate at the Center for Education Quality Assurance in West Sumatra Province is in the good category, with an overall average value of 4.27. The employee motivation indicator received the highest average score of 4.38, followed by the work coordination indicator at 4.25, the work environment indicator at 4.24, and the communication indicator at 4.23. Research findings indicate that the organizational climate at the West Sumatra Provincial Center for Education Quality Assurance has been able to create working conditions that support employee performance through good work coordination, high employee motivation, a conducive work environment, and effective communication. Therefore, the organization needs to maintain a good organizational climate and continuously improve the quality of communication and coordination between work units to support organizational effectiveness and optimal goal achievement.